An Analysis of cis-Acting Regulatory Elements Related to Light Response in the 5’ Flanking Region of the Ascocenda and Dendrobium Actin Genes - Wuthipong, Pangjai; Huehne, Pattana Srifah (Agriculture and Natural Resources, 2015)
In a previous study, the rice actin promoter was considered as a constitutive promoter, which could drive reporter gene expression in orchid flowers. Therefore, in this study, the 5’ flanking regions of the actin genes isolated from Ascocenda Princess Mikasa ‘Blue’ and Dendrobium Jacquelyn Thomas ‘UH44-50’ orchids were validated for predicted cis-acting regulatory elements (CAREs) using the PlantCARE program and the PLACE database. A high frequency of predicted CAREs, which were distinct in numbers and locations, particularly the CAREs that respond to light, was found within the upstream flanking regions of the actin gene in orchids, rice and banana. Both orchid upstream sequences contained some predicted CAREs that are predominantly involved in light regulation. When orchid flowers were exposed to different light periods, the expression of vegetative actin in Ascocenda flower tissues (column, lip and petal) was completely up-regulated, as determined by qualitative real-time polymerase chain reaction. In addition, all of the 5’ flanking regions of orchid, rice and banana actin genes contained large numbers of the transcriptional control sequences, TATA boxes, which were composed of similar sequences to the conserved TATA box of vegetative actin. The further investigation of the 5’ flanking region of orchid actins for their activities will be essential in the development of these promoter regions for biotechnological use.